Social determinants of therapy failure and multi drug resistance among people with tuberculosis: A review. (March 2017) - Di Gennaro, Francesco; Pizzol, Damiano; Cebola, Bonifacio; Stubbs, Brendon; Monno, Laura; Saracino, Annalisa; Luchini, Claudio; Solmi, Marco; Segafredo, Giulia; Putoto, Giovanni; Veronese, Nicola
Abstract: Background: Social determinants influence health and the development of tuberculosis (TB). However, a paucity of data is available considering the relationship of social determinants influencing therapy failure and multi drug resistance (MDR). We conducted a review investigating the relationship of common social determinants on therapy failure and MDR in people with TB. Methods: PubMed and SCOPUS were searched without language restrictions until February 02, 2016 for studies reporting the association between socioeconomic factors (income, education and alcohol abuse) and therapy failure or MDR-TB. The association between social determinants and outcomes was explored by pooling data with a random effects model and calculating crude and adjusted odds ratios (ORs) ±95% confidence intervals (CIs). Results: Fifty studies with 407, 555 participants with TB were included. Analysis demonstrated that low income (unadjusted OR = 2.00 (95% CI: 1.69–2.38; I 2 = 88%; 33 studies, adjusted OR 1.77, p < 0.0001), low education (unadjusted OR 2.11, 95% CI 1.55–2.86, 26 studies, adjusted OR 1.69, p < 0.0001) and alcohol abuse (unadjusted OR = 2.43 (95% CI: 1.56–3.80, 16 studies, adjusted OR 2.13, p < 0.0001) were associated with therapy failure. Similarly, low income (unadjusted OR = 1.67; 95% CI: 1.12–2.41, p = 0.006; 14 studies, adjusted OR 2.16, p < 0.0001) and alcohol abuse (unadjusted OR = 1.88; 95% CI: 1.18–3.00, 7 studies, adjusted OR 1.43, p = 0.06) were associated with MDR-TB. Increasing age of the population was able to explain a consistent part of the heterogeneity found.